Clinical characteristics and outcomes of 56 patients with pneumonia caused by carbapenem-resistant Klebsiella pneumoniae. (June 2021) - Chen, I-Ren; Huang, Po-Han; Wu, Ping-Feng; Wang, Fu-Der; Lin, Yi-Tsung
Highlights: Clinical and microbiological characteristics of pneumonia caused by carbapenem-resistant Klebsiella pneumoniae (CRKP). 7-day and 14-day mortality rates were 7.1% and 23.2%, respectively, in 56 patients with monomicrobial CRKP pneumonia. Malignancy and APACHE II score were independently associated with 14-day mortality. ABSTRACT: Objectives: Pneumonia caused by carbapenem-resistant Klebsiella pneumoniae (CRKP) is associated with high mortality. However, clinical studies on CRKP infections often exclusively involve bacteraemia, with only a few studies having focused on pneumonia. This retrospective study was conducted to investigate the clinical and microbiological characteristics of pneumonia caused by CRKP. Methods: Adult patients diagnosed with CRKP monomicrobial pneumonia treated with at least one active antimicrobial agent within 5 days of the pneumonia diagnosis were identified in a medical centre in Taiwan between January 2017 and April 2019. Clinical characteristics and outcomes of these patients were determined. Resistance mechanisms and capsular types of the CRKP isolates were determined by PCR. Results: A total of 56 patients with CRKP monomicrobial pneumonia were identified. The 7-day and 14-day mortality rates were 7.1% and 23.2%, respectively. Malignancy [adjusted odds ratio (aOR) = 8.87, 95% confidence interval (CI) 1.66–47.26; P  = 0.011] and Acute Physiology and Chronic Health Evaluation (APACHE) II score (aOR = 1.12, 95% CI 1–1.25; P  = 0.048) were independently associated with 14-day mortality. Most CRKP clinical isolates were carbapenemase-producers (39/44; 88.6%), of which K. pneumoniae carbapenemase type 2 (KPC-2)-producing isolates were most prevalent (30/39; 76.9%). The most prevalent capsular type in these isolates was K47 (30/44; 68.2%). Conclusion: CRKP pneumonia is associated with high 14-day mortality. Malignancy and APACHE II score were independently associated with 14-day mortality.